Recalibration of eddy viscosity models for numerical simulation of cavitating flow patterns in low pressure nozzle injectors - Coussirat, Miguel; Moll, Flavio (My University, 2021)
Cavitation in pressure injectors/atomizers affects the liquid/spray jet behavior at its outlet. The type of atomization induced by cavitation allows developing efficient devices if this cavitation state is controlled. Cavitating flow is related to turbulent and multiphase flows with mass transfer between the liquid and its gaseous phase and which is affected by several factors. Due to the high-speed flow and small spatial and time scales involved, the study of cavitating flows using physical experiments is very expensive. By means of numerical simulations using eddy viscosity models, some of the incipient and slight developed cavitating flow characteristics in nozzles are captured, but the level of the vapor fraction is commonly underestimated. It is evident that a suitable calibration of the turbulence models based on the special characteristics of the incipient/slight developed cavitating flows allows obtaining improved results. This special calibration is necessary due to the close relation between the cavitation inception/developing conditions and the turbulence level in the flow leading to a “nonstandard turbulence state.” So, cavitating flows should not be modeled as a simple turbulent one. It is also demonstrated that the results obtained become competitive compared against the ones computed by large eddy simulations, which need a lot of computational resources and an appropriate initial solution for running. The conclusions obtained can be useful to improve injector designs because the suitable simulation of the incipient cavitation or slight developed cavitation flow conditions can be accurately simulated after calibration.
Keywords: Avitation, Turbulence, Eddy viscosity models, Validation/calibration, Nozzle injectors